Pembelajaran Bahasa Indonesia Bagi Anak Disleksia Kelas IV di SDN 15 Pulai Anak Air Bukittinggi Pada Masa Pandemi Covid-19 - Deri April Ningsih; Asep Ahmad Sopandi (Universitas Negeri Padang, 2021)
This research was motivated by the discovery of a problem at SDN 15 Pulai Anak Air regarding learning Indonesian for grade IV dyslexic children during the Covid-19 pandemic. This situation makes the learning change to distance learning. So the researchers are interested in knowing more about how to learn Indonesian for fourth grade dyslexic students at SDN 15 Pulai Anak Air during the Covid-19 pandemic. This study used descriptive qualitative method. The research subjects were homeroom teachers, dyslexic students and school principals. Collecting data using interviews, observation and documentation. The results showed that learning Indonesian for dyslexic children during the Covid-19 pandemic was carried out online and offline. The process of learning Indonesian for dyslexic children includes 1) learning planning including assessment, syllabus and RPP; 2) the implementation of learning includes preliminary activities, core activities, closing and assessment/evaluation. Learning constraints during the Covid-19 pandemic are in compiling a syllabus and developing online learning materials for dyslexic children.